South-Western Federal Taxation 2020: Corporations, Partnerships, Estates and Trusts, 43rd Edition - William A. Raabe; James C. Young; William H. Hoffman (Cengage Learning, 2019)
Master today's tax concepts and gain a thorough understanding of current tax legislation with SOUTH-WESTERN FEDERAL TAXATION 2020: CORPORATIONS, PARTNERSHIPS, ESTATES & TRUSTS, 43E. This complete, reader-friendly book helps you master tax concepts impacting contemporary corporations, partnerships, estates and trusts. You examine the most current tax legislation at the time of publication, including tax reforms of 2018 and the Tax Cuts and Jobs Act of 2017. Engaging learning features, such as ""Big Picture"" examples, memorable tax scenarios and helpful summaries further clarify concepts. These features also strengthen critical-thinking, writing and online research skills that are key to your success as a tax practitioner. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.